Implementasi Pembelajaran Baca Tulis Al-Quran Untuk Meningkatkan Kemampuan Membaca Dan Menulis Al-Quran Di SDN Pangkatrejo - ahdah, siti aisyah; Sholihah, Khotimatus; Shoimah, Retno Nuzilatus (Jurnal Murid, 2024)
Reading and Writing Al-Qur'an (BTQ) is an initial stage that must be taken to deepen the religion of Islam. Learning to read and write the Qur'an should be taught to every Muslim student at all levels of education, both formal and non-formal education. The purpose of writing this article is (1) to find out the implementation of learning to read and write the Koran to improve the ability to read and write the Koran at SDN Pangkatrejo. (2) to find out the supporting and inhibiting factors of learning to read and write the Koran. The design used in this research is field research. Data collection tools using interviews, observation and documentation. The data analysis technique uses qualitative data analysis techniques based on Miles and Hubermean theory which consists of three stages, namely data reduction, data display and conclusion/verification. The design used in this research is field research. Data collection tools using interviews, observation and documentation. The data analysis technique uses qualitative data analysis techniques based on Miles and Hubermean theory which consists of three stages, namely data reduction, data display and conclusion/verification. Learning to Read and Write the Al-Quran at SDN Pangkatrejo is carried out in the form of learning tajwid rules, practicing the pronunciation of hijaiyyah letters fluently, and reading the Al-Quran and An Nahdliyah Book which consists of 6 volumes directly in front of the teacher. Supporting and inhibiting factors that occur in learning to read and write the Koran are teachers, students and the surrounding environment. The conclusion from the discussion is that learning to read and write the Koran is a lesson that learns to read and write the Koran so that students are smarter in learning to read and write the Koran. Supporting and inhibiting factors that occur in learning to read and write the Koran are teachers, students and the surrounding environment.